2002
DOI: 10.1021/cm0102739
|View full text |Cite
|
Sign up to set email alerts
|

Sol-Hydrothermal Synthesis and Hydrothermally Structural Evolution of Nanocrystal Titanium Dioxide

Abstract: A sol-hydrothermal method has been proposed to prepare uniform and unaggregated nanocrystals of pure anatase and rutile from various acidic mediums. The phase formation, particle sizes, and morphologies varying with different acids and their concentrations at different reaction temperatures and times have been investigated using X-ray diffraction and transmission electron microscopy. The use of HCl and the effect of its concentrations on the formation of rutile phase at different temperatures for various react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
201
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(214 citation statements)
references
References 50 publications
10
201
1
2
Order By: Relevance
“…In acidic or basic medium, a fraction of the product usually consists of rutile and brookite phases of TiO 2 which may reduce the activity of the catalyst. [14,15] In bulk materials, Raman modes obey the fundamental selection rule q D 0, where 'q' is the wave vector of the scattered phonon. In the case of crystals of very small size, this rule is no longer valid as the phonons are spatially confined and the phonons all over the Brillouin zone will contribute to the first-order Raman scattering.…”
Section: Micro Raman Analysismentioning
confidence: 99%
“…In acidic or basic medium, a fraction of the product usually consists of rutile and brookite phases of TiO 2 which may reduce the activity of the catalyst. [14,15] In bulk materials, Raman modes obey the fundamental selection rule q D 0, where 'q' is the wave vector of the scattered phonon. In the case of crystals of very small size, this rule is no longer valid as the phonons are spatially confined and the phonons all over the Brillouin zone will contribute to the first-order Raman scattering.…”
Section: Micro Raman Analysismentioning
confidence: 99%
“…Different methods have been employed for the synthesis of titanium dioxide, as follows: chemical precipitation (Pedraza and Vasquez, 1999;Scolan and Sanchez,1998), the sol-gel method (Gartner et al, 2004;Su et al, 2006b), hydrothermal (Wu et al, 2002) and solvothermal processes (Kim et al, 2003;Yin et al, 2003), combustion method (Nagaveni et al, 2003), a microemulsion-mediated process (Hong et al, 2003), electrochemical synthesis , fungus-mediated synthesis (Jha et al, 2009) and chemical vapour deposition (CVD) (Jones and Chalker 2003). Venkatachalam et al (2007) reported the preparation of titanium dioxide nanoparticles via the sol-gel method with different reaction parameters, such as different hydrolyzing agents, molar ratio, aging time and calcination temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the pure anatase phase suggests negligible effect of Cl -, NO 3 -and ClO 4 -anions on the TiO 2 phase formation even though these species are known to stabilize rutile and brookite. [16][17][18] The SAXRD of TiO 2 and TiO 2 HA1M ( Figure 1B) shows a broad intense peak centered at 1.5°. Although the Bragg reflections of the space group are not resolved, the presence of a low angle diffraction peak suggests that the samples possess a semi-organized mesoporous structure with relative uniform pores, but without long range ordering.…”
Section: Resultsmentioning
confidence: 99%